Teamwork and Clinical Error Reporting among Nurses in Korean Hospitals - Jee-In Hwang, PhD; Jeonghoon Ahn, PhD (Elsevier, 2015)
Purpose: To examine levels of teamwork and its relationships with clinical error reporting among Korean hospital nurses. Methods: The study employed a cross-sectional survey design. We distributed a questionnaire to 674 nurses in two teaching hospitals in Korea. The questionnaire included items on teamwork and the reporting of clinical errors. We measured teamwork using the Teamwork Perceptions Questionnaire, which has five subscales including team structure, leadership, situation monitoring, mutual support, and communication. Using logistic regression analysis, we determined the relationships between teamwork and error reporting. Results: The response rate was 85.5%. The mean score of teamwork was 3.5 out of 5. At the subscale level, mutual support was rated highest, while leadership was rated lowest. Of the participating nurses, 522 responded that they had experienced at least one clinical error in the last 6 months. Among those, only 53.0% responded that they always or usually reported clinical errors to their managers and/or the patient safety department. Teamwork was significantly associated with better error reporting. Specifically, nurses with a higher team communication score were more likely to report clinical errors to their managers and the patient safety department (odds ratio = 1.82, 95% confidence intervals [1.05, 3.14]). Conclusions: Teamwork was rated as moderate and was positively associated with nurses' error reporting performance. Hospital executives and nurse managers should make substantial efforts to enhance teamwork, which will contribute to encouraging the reporting of errors and improving patient safety.